Maternal and perinatal outcome in postdated pregnancy: a study of 100 cases in Bangladesh armed forces (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Any pregnancy which has passed beyond the Expected Date of Delivery (EDD) is called postdated pregnancy or prolonged pregnancy. But when pregnancy has prolonged beyond 42 weeks are called postmaturity or post term pregnancy. Incidence of prolonged pregnancy is 3-14 % of all gestations. Aim: The aim of the study is to determine the foetal and maternal outcome and complications in patients presenting with postdated pregnancy in Combined Military Hospital of Bangladesh Armed Forces. Materials & Methods: A cross-sectional study was conducted for one year at the Department of Gynecology and Obstetrics in Combined Military Hospital, Dhaka. During this period total 100 cases were studied. Cases were selected randomly. Here postdatism was applied to any pregnancy which exceeded the EDD and it also included postmaturity which is pregnancy extending beyond 42 completed weeks. A preformed proforma was used to collect data which were analyzed later on. Results: Amongst 1853 cases of labour patients, 273 cases were postdated pregnancy and 169 cases postmaturity. The incidence of postdated pregnancy in this series was 15% and postmaturity was 9.14%. 93% patients had regular antenatal checkup. 82% patients were presented not in labour situation. 60% cases were NVD and 40% cases LUCS was done. No craniotomy or forceps was required. There was no maternal death. But there were two Intra Uterine Deaths (IUD) and one neonatal death due to umbilical sepsis. 39 JAFMC Bangladesh. Vol 10, No 1 (June) 2014 Conclusion: Any pregnancy that goes beyond 41 weeks of confirmed gestational age foetal well-being must be assessed. Proper management is a pre-requisite to reduce the rate of perinatal mortality and morbidity in this group of patient. DOI: http://dx.doi.org/10.3329/jafmc.v10i1.22903 Journal of Armed Forces Medical College Bangladesh Vol.10(1) 2014